Gamification Marketing and Service Quality in Student Enrollment Decisions: Gamification Marketing dan Kualitas Layanan dalam Keputusan Pendaftaran Mahasiswa - Mulyandi, M. Rachman; Lapian, Michelle Elise; Hartadi, Haris; Santoso, Swaniesha Ophelia (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The growing number of private universities in Banten Province has intensified competition for student recruitment. Specific background: Universities have adopted gamification marketing and improved service quality to attract potential students, but their effectiveness in higher education remains unclear. Knowledge gap: Previous studies have mainly examined these strategies in retail and e-commerce sectors, leaving limited evidence in the educational context. Aim: This study investigates how gamification marketing using game-based learning and university service quality relate to students’ enrollment decisions. Results: Quantitative analysis with 240 respondents revealed that both gamification marketing and service quality showed a very small and statistically insignificant relationship with enrollment decisions (R² = 13%, p > 0.05). Novelty: The findings challenge prior studies by showing that gamification and service quality, though well-designed, do not directly influence student decision-making in short-term exposure. Implications: Universities should continue employing gamified marketing and service enhancement as complementary strategies while exploring other influential factors such as reputation, tuition fees, and career prospects. • Gamification marketing and service quality show minimal association with student enrollment.• Game-based learning offers engagement benefits but limited short-term behavioral outcomes.• Further studies should explore long-term effects and additional influencing factors. Keyword Gamification Marketing, Game-Based Learning, University Service Quality, Student Enrollment, Higher Education